WASC Substantive Change Screening Form: CSUCI School of Education Master of Science in School Psychology (with Pupil Personnel Services Credential)
competencies required for the California Pupil Personnel Services Credential (Credential Code: 00802). This credential authorizes the holder to function as a school counselor in grades K through 12. Applicant must apply for the Master of Science in School Counseling and the California Pupil Personnel Services Credential (Credential Code: 00802). Additional information may be obtained from the Department of Educational Leadership & School Counseling & Psychology at this link: [TBD] Students plan the sequence of the degree in consultation with the program coordinator and advisor. The M. S. and credential have a minimum of 60 units of 600- numbered courses which are listed on the degree roadmap.